The expressions have to be solved and expressed in the lowest terms.

`3/(u+3) + u - 2`

=> `(3 + (u - 2)(u + 3))/(u + 3)`

=> `(3 + u^2 - 2u + 3u - 6)/(u + 3)`

=> `(u^2 + u - 3)/(u + 3)`

`5/(x + 3) + 1/(x^2 - 9)`

=> `(5(x - 3) + 1)/(x^2 - 9)`

=> `(5x - 15 + 1)/(x^2 - 9)`

=> `(5x - 14)/(x^2 - 9)`

`2/(sqrt(x^2 + 2)) - 5/(x^2+2)`

=> `(2*sqrt(x^2 + 2) - 5)/(sqrt(x^2 + 2))`

=> `(2*sqrt(x^2 + 2) - 5)/(sqrt(x^2 + 2))`

=> `(2*(x^2 + 2) - 5*sqrt(x^2 + 2))/(x^2 + 2)^(3/2)`

=> `(4x^2 + 4 - 5*sqrt(x^2 + 2))/(x^2 + 2)^(3/2)`

**The expressions in the lowest terms are: `3/(u+3) + u - 2 = (u^2 + u - 3)/(u + 3)` , `5/(x + 3) + 1/(x^2 - 9) = (5x - 14)/(x^2 - 9)` and **`2/(sqrt(x^2 + 2)) - 5/(x^2+2) = (4x^2 + 4 - 5*sqrt(x^2 + 2))/(x^2 + 2)^(3/2)`

## We’ll help your grades soar

Start your 48-hour free trial and unlock all the summaries, Q&A, and analyses you need to get better grades now.

- 30,000+ book summaries
- 20% study tools discount
- Ad-free content
- PDF downloads
- 300,000+ answers
- 5-star customer support

Already a member? Log in here.

Are you a teacher? Sign up now